Abrikossoff tumor: rare dermatosis in a case with epidemiological and therapeutic specificities - Carolina D. Cruz; Elizabeth L. Fernandes; Sergio F. de S. Cunha; Adriana R. Beltrão; André C.A.F. Pessanha (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Granular cell tumor is a rare benign neoplasm, which preferentially affects the oral cavity, more common in adults and rare in children. This report is about a 9-year-old patient with a painful periungual nodule of the fifth finger of the right hand, with two years of evolution. The anatomopathological examination revealed an Abrikossoff tumor, without bone involvement on X-ray and positive markers on immunohistochemistry. Due to the location of the lesion, Mohs micrographic surgery was chosen in order to have greater tissue preservation and local functionality. There was no recurrence of the tumor, with resolutive surgery and satisfactory aesthetic results.